CHILDREN'S MINDS TALKING RABBITS & CLOCKWORK ORANGES: ESSAYS ON EDUCATION (Author: Kieran Egan) - Russell, Reviewed by: Joan (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2000)
KIERAN EGAN. Children's Minds Talking Rabbits & Clockwork Oranges: Essays on Education. London, Ontario: The Althouse Press (1999). 200 pp. $24.95 (paper) (ISBN: 0-920354-46-7).